The Predictive Role of MMP-2, MMP-9, TIMP-1 and TIMP-2 Serum Levels in the Complete Response of the Tumor to Chemotherapy in Breast Cancer Patients - Kayhan Ozdemir; Ismail Zengin; Gamze Guney Eskiler; Havva Belma Kocer; Asuman Deveci Ozkan; Tayfur Demiray; Elif Ozozen Sahin (Journal of Investigative Surgery, 2022)
Objective We investigated the serum levels of MMPs and TIMPs in breast cancer (BC) patients to predict the response rate to/after treatment with or without neoadjuvant chemotherapy. BC is the most common cancer in women and MMPs are responsible for the breakdown of ECM proteins during organogenesis and TIMPs are restricted the ECM destruction by MMPs. However, the predictive role of MMPs and TIMPs in the treatment response of BC patients has not identified. Methods This study consisted of 96 BC patients (34 neoadjuvant treatment and 62 surgically treated) and 35 healthy individuals. ELISA was used to determine the level of MMP-2, MMP-9, TIMP-1, and TIMP-2 from serum samples of BC patients. Results The mean levels of MMP-9 and TIMP-2 were significantly increased in all BC patients at diagnosis and after chemotherapy, but MMP-2 was considerably lower at diagnosis. There was only a significant difference in the TIMP-1 levels after chemotherapy as well as HER2 and ER status in the neoadjuvant and surgically treated group. Additionally, MMP-2 and MMP-9 serum levels negatively correlated with tumor size and metastatic lymph nodes in BC patients after chemotherapy. Conclusions BC patients with high levels of MMP-9 and TIMP-2 can be used to predict the stage of the tumor and CR to chemotherapy and higher TIMP-1 serum level after chemotherapy could be related to better response to chemotherapy.